Развитие медиакомпетентности учащихся посредством видеосъёмки с элементами театрализации - Жданько, Анна Павловна (Rossijskij psihologičeskij žurnal., 2010)
The article proves the current importence and effectiveness of video filming with elements of theatricalization as a means of the development of mediacompetence and linguadidactic communicative competence. The value of mediaeducation integrated in the foreign languages’ teaching under the conditions of influence of civilization’s technological achievements and modern means of communication (computer technologies, video, etc.) is underlined. The essence of philosophical theory which is the base for a possible analyses of the development of pupils’ mediacompetence and linguadidactic communicative competence is revealed. В статье обоснована актуальность и эффективность использования видеосъёмки с элементами театрализации как средства формирования лингводидактической коммуникативной компетентности и медиакомпетентности. Подчёркивается значимость интеграции медиаобразования в преподавание иностранного языка в условиях влияния технологических достижений цивилизации и средств современной коммуникации (компьютерных технологий, видео и т.д.).Раскрывается сущность философской теории, на базе которой возможен анализразвития медиакомпетентности и иноязычной коммуникативной компетентности учащихся.